Utility of Panoramic Radiograph for Assessment of Mandibular Asymmetry as Compared with Posteroanterior Cephalogram - Muhammad Afrasiab Khan, Asif Haider, Muhammad Noman, Faiza, Sarah Sabir, Abid Ali, Noman Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Was to assess the mandibular asymmetry on panoramic radiograph (OPG) as compared to PA (posterior anterior) cephalogram. Materials and method: A total of 15 participant’s records with age above 12 years; both genders; Pakistani nationals; clear OPG and PA cephalogram available; and full biodata available were included. Radiographs of participants with unerupted or missing teeth in anterior or posterior region were excluded. Three linear measurements (condylar, ramus, and body length) and one angular measurement (gonial angle) were performed on both OPG and PA cephalograms. Paired t test and Pearson correlation test were applied between OPG and PA cephalogram for condylar, ramus, and body length and gonial angle to see the relationship. Results: The females were 6(40%) and males were 9(60%). The mean condylar length measured on OPG was 8.44 ± 2.96mm and on PA cephalogram was 9.98 ± 2.73mm with mean difference of 1.5mm and no statistical difference (p=0.1007). Similarly the ramus length (p=0.706), corpus length (p=0.066) and gonial angle (p=0.333) were not statistically different measured on OPG and PA cephalogram. Very high correlation was found for measurements on OPG and PA cephalogram for condylar length(r=0.97), ramus length (r=0.96), body length (r=0.93) and was very highly statistically significant (p<0.001). But the correlation for gonial angle was moderate and not statistically significant (p=0.035). Conclusion: The panoramic radiograph can be used for initial diagnosis of mandibular asymmetry. Keywords: Mandibular asymmetry, panoramic radiograph, posterior-anterior cephalogram